STRATEGI MEMERANKAN KOPERASI MAHASISWA SEBAGAI WADAH PENDIDIKAN DAN PENGEMBANGAN JIWA KEWIRAUSAHAAN YANG PEDULI NILAI - Tri Kurniawati, (Pendidikan Ekonomi, 2011)
Entrepreneurship education is one aspect of education that is directed to produce individuals who are able to seize opportunities and create new economic activity. Entrepreneurship education will equip students with entrepreneurial spirit and sufficient life skill to build new business. Implementation of entrepreneurship education can be developed by utilizing the students cooperative institution. Entrepreneurship education is done through two channels. Entrepreneurship education is first developed in the internal cooperative students through formal, nonformal and informal. Second, cooperatives are used as a laboratory for students to conduct entrepreneurial lectures.